Pretreatment intracerebral and peripheral blood immune responses in Vietnamese adults with tuberculous meningitis: Diagnostic value and relationship to disease severity and outcome - Simmons, Cameron (2018)
Tuberculous meningitis (TBM) is the most devastating form of tuberculosis. Both intracerebral and peripheral blood immune responses may be relevant to pathogenesis, diagnosis, and outcome. In this study, the relationship between pretreatment host response, disease phenotype, and outcome in Vietnamese adults with TBM was examined. Before treatment, peripheral blood IFN-gamma ELISPOT responses to the Mycobacterium tuberculosis Ags ESAT-6, CFP-10, and purified protein derivative (PPD) were a poor diagnostic predictor of TBM. Cerebrospinal fluid IL-6 concentrations at presentation were independently associated with severe disease presentation, suggesting an immunological correlate of neurological damage before treatment. Surprisingly however, elevated cerebrospinal fluid inflammatory cytokines were not associated with death or disability in HIV-negative TBM patients at presentation. HIV coinfection attenuated multiple cerebrospinal fluid inflammatory indices. Low cerebrospinal fluid IFN-gamma concentrations were independently associated with death in HIV-positive TBM patients, implying that IFN-gamma contributes to immunity and survival. Collectively, these results reveal the effect of HIV coinfection on the pathogenesis of TBM and suggest that intracerebral immune responses, at least in HIV-negative cases, may not be as intimately associated with disease outcome as previously thought.